Formation of the oxide fume and aerosol dispersal from the oxidation of uranium metal at temperatures less than 1000 °C - Clark, Douglas Kristopher (Kansas State University, 2009)
The reaction chemistry of uranium metal has been well documented for use in the development of nuclear fuels. The oxidation of uranium from the thermal stress of nearby combustion is different than that of a reactor environment due to the selectivity of the various competing reactions. This work extracts available information in literature and various experiments over the last 60 years to provide a critical look at the response of uranium metal to thermal stress. The oxide fume formed and the equilibrium phase shifts during the dispersal of the airborne particulate are of principal interest when determining potential consequences to the health and safety of the workers, members of the public, and the environment. The transport phenomena and reaction kinetics of the oxide fume are also discussed at various distances from the source material. Uranium is a versatile element that can form numerous compounds, of which the oxides are the forms that are most readily generated under thermal stress and also pose the largest health risk to human beings, primarily through inhalation. A general summary of uranium and the dry compounds (oxides and carbides) is provided discussing the different structures of each state. The reaction kinetics and selectivity as the oxidation progresses is discussed for typical uranium metal forms at temperatures above and below the ignition point. Characteristics of potential fires are qualified for determining thermal stress. The creation of the oxide fume is outlined followed by dispersal characteristics of the aerosol. These molecular processes are related to the release fractions of uranium under fire scenarios which are compared with available experimental data from the regulatory handbooks. A critical look at the conclusions of the handbook with recommendations for revising the existing guidelines and additional testing are made in the interest of ensuring that derived controls are appropriate to reduce the risk of accidents involving the oxidation of uranium metal.
Keywords: Airborne Release Fraction; Uranium; Chemistry, Nuclear (0738); Chemistry, Physical (0494); Engineering, Chemical (0542)